Efecto del uso de aceite de cannabis sobre los parámetros productivos en Pollos de engorda Broiler Cobb 500 - Mosquera Rodríguez, Jairo Andrés (2024)
The research evaluated the impact of cannabis oil on the feed of Broiler Cobb 500 chickens, considering both productive and organoleptic aspects. A random experiment was conducted with 120 chickens divided into four groups: one control with pure water and three with different concentrations of cannabis oil (1 ml, 2 ml, and 3 ml). For six weeks, parameters such as food intake, weight gain, and feed conversion were measured. Data were analyzed with two-way ANOVA and Tukey’s test, allowing detailed comparisons between treatment groups. The results showed that cannabis oil in Broiler Cobb 500 chicken diet had a positive effect on feed intake and weight gain, especially highlighting the group treated with 2 ml cannabis oil. This group showed significant improvements in food conversion and proved to be the most cost-effective in the cost-benefit analysis, outperforming the control group and the other treated groups. Sensory analyzes confirmed that the cannabis oil did not negatively affect the quality of the meat in terms of taste, smell and texture, maintaining an acceptable profile for consumption.In addition, the research addressed ethical and safety aspects, ensuring that the use of the cannabis oil will comply with legal regulations and will not pose health risks to consumers. The obtained data provide valuable information to improve the sustainability and profitability of the poultry industry in Ecuador, and open the door for future research on the potential of cannabis oil in animal feed